2011
DOI: 10.1063/1.3662127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spanwise confinement on flag flutter: Experimental measurements

Abstract: International audienceThe effect of spanwise clearance on the critical velocity for fluttering of a cantilevered plate in a channel flow is addressed experimentally. It is found that the critical velocity is influenced by the presence of the walls when the ratio between the clearance and the length of the plate C/L is less than 0.1 and slowly converges to the critical velocity predicted by models considering infinite span plates. These results are in good agreement with the predictions of a potential flow mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…They found a significant 3D effect on the vortical structures for smaller span, and its stabilizing influence through a reduction of the pressure difference across the flag. Doare, Mano & Ludena (2011) show that a 2D model always underestimates the critical velocity relative to 3D experimental data. By bounding the flexible plate between two spanwise walls, they are able to quantify the difference due to 3D spanwise effects.…”
Section: Introductionmentioning
confidence: 91%
“…They found a significant 3D effect on the vortical structures for smaller span, and its stabilizing influence through a reduction of the pressure difference across the flag. Doare, Mano & Ludena (2011) show that a 2D model always underestimates the critical velocity relative to 3D experimental data. By bounding the flexible plate between two spanwise walls, they are able to quantify the difference due to 3D spanwise effects.…”
Section: Introductionmentioning
confidence: 91%
“…The objective of covering only one third of the width of the plate with piezoelectric film is to reduce the impact of the sectioning process on the global rigidity of the plate. For each experiment and a given electrode length and position, the experimental procedure is as follows : the piezoelectric plate is placed in a wind tunnel of rectangular transversal section 10 cm wide and 5 cm high with transparent walls that allow visual access from the outside [40]. The negative electrodes of the piezoelectric films are shunted while a resistance R is connected between the positive electrodes (see figure 3-d).…”
Section: Optimization Of the Electrodes' Positionmentioning
confidence: 99%
“…These studies report a strong correlation between the distance of the plate to the channel walls and the dynamics of the plate. The three-dimensional effects of confinement in the spanwise direction have been studied experimentally (Doaré, Mano & Ludena 2011a) and also analytically (Doaré, Sauzade & Eloy 2011b) and it has been concluded that the reduction in the gap between the plate and the walls in the spanwise direction has a destabilizing effect on the dynamics of the system, especially for plates with larger inertia. Finally, Auregan & Depollier (1995) used a quasi-static frictionless fluid model to study a similar problem of aeroelastic instability of the human soft palate and provided an explanation for the occurrence of snoring.…”
mentioning
confidence: 98%